An interesting case of systemic lupus erythematosus presenting with hypercalcemia: A diagnostic dilemma - Abdul Gafor, Abdul Halim (International Scientific Literature, Inc., 2013)
BACKGROUND: Hypercalcemia is common in primary hyperparathyroidism malignancies and even in tuberculosis. Interestingly, systemic lupus erythematosus (SLE) rarely presents with hypercalcemia. CASE REPORT: We describe an interesting case of SLE in a patient who was otherwise thought to have either tuberculosis or a malignancy. The patient initially presented with feeling unwell, with generalized lymphadenopathy, bilateral pleural effusion, and bilateral corneal calcium deposits secondary to severe hypercalcemia. The diagnosis of SLE was made based on positivity of antinuclear antibodies (ANA) and anti-dsDNA, the presence of serositis, lymphadenopathy, autoimmune hemolytic anemia, and constitutional symptoms. She was treated with steroids, with tremendous improvement in her general well-being, resolution of lymphadenopathy and pleural effusion, and normalization of her hemoglobin and serum calcium. The atypical presentation of SLE with hypercalcemia with pleural effusion is discussed. CONCLUSIONS: SLE should be one of the differential diagnoses in patients presenting with severe hypercalcemia.